COVID-19 Viral Pneumonia Complicated with Acute Pulmonary Embolism: A Descriptive Study - Hoda Salah Darwish; Mohamed Yasser Habash; Waleed Yasser Habash (Radiology Research and Practice)
Objective. To evaluate acute pulmonary embolism in patients with 2019 novel coronavirus (COVID-19) pneumonia using pulmonary CT angiography. Subjects and Methods. From 95 symptomatic patients confirmed with COVID-19 by RT-PCR from 1 May to 14 July 2020 in Dallah Hospital, Riyadh, Saudi Arabia, CT angiography was done for 25 patients suspected to have pulmonary embolism and have no contraindication for contrast study. 11 cases of them showed CT evidence of acute pulmonary embolism (PE). Retrospectively, CT angiography was analyzed and detailed findings were recorded. This study was approved by the Institutional Review Board of our hospital, and the patient consent was waived. Results. The mean age of the included patients was 49 ± 11 years; the youngest was 22 years, and the oldest was 64 years. Common symptoms in the 25 cases that underwent CT angiography were fever that was noted in 21/25 cases (84%), shortness of breath in 18/25 cases (72%), cough in 16/25 cases (64%), and severe myalgia/body fatigue in 13/25 cases (52%). The less common symptoms were sore throat in 11/25 cases (44%) and headache in 10/25 cases (40%). Regarding CT findings, 4/25 cases (16%) had unilateral lung disease and 21/25 cases (84%) had bilateral disease, with slight predilection for the right lower lobe (10/25 cases, 40%). Pure ground-glass opacity (GGO) was seen in 13/25 cases (52%), and GGO with consolidation was seen in 12/25 cases (48%). Common accompanying CT signs included crazy paving stone sign in 15/25 cases (60%) and air bronchogram in 12/25 cases (48%). From the 25 patients that showed respiratory deterioration and elevated serum D-dimer level, 11 cases confirmed to have acute pulmonary embolism, while 14 cases showed negative result for pulmonary embolism. 6/11 were male and 5/11 were female. Pulmonary embolism was diagnosed at a mean of 21 days from symptom onset. Unilateral acute pulmonary embolism was seen in 3/11 cases, while 8/11 cases showed bilateral distribution. Among 11 cases with acute pulmonary embolism, no emboli at the central level could be seen, but 3 cases showed pulmonary embolism at the lobar level, 3 cases at the segmental level, and 5 cases at lobar, segmental, and subsegmental levels. Conclusion. In patients with confirmed COVID-19, we should maintain a high suspicion for its thromboembolic complications such as acute pulmonary embolism that was mainly diagnosed at the end of 3rd week from symptom onset. We suggest that whenever a CT evaluation of the parenchymal involvement of COVID-19 pneumonia is performed, a simultaneous evaluation of the pulmonary arteries is also essential in order to identify early signs of associated pulmonary embolism.